The limit of dynamic voltage scaling and insomniac dynamic voltage scaling. - Bo Zhai (IEEE Transactions on VLSI systems)
Dynamic voltage scaling (DVS) is a popular approach for energy reduction of integrated circuits. Current processors that use DVS typically have an operating voltage range from full to half of the maximum Vdd. However, there is no fundamental reason why designs cannot operate over a much larger voltage range: from full Vdd to subthreshold voltages. This possibility raises the question of whether a larger voltage range improves the energy efficiency of DVS. First, from a theoretical point of view, we show that, for subthreshold supply voltages, leakage energy becomes dominant, making "just-in-time computation" energy-inefficient at extremely low voltages. Hence, we introduce the existence of a so-called "energy-optimal voltage" which is the voltage at which the application is executed with the highest possible energy efficiency and below which voltage scaling reduces energy efficiency. We derive an analytical model for the energy-optimal voltage and study its trends with technology scaling and different application loads. Second, we compare several different low-power approaches including MTCMOS, standard DVS, and the proposed Insomniac (extended DVS into subthreshold operation). A study of real applications on commercial processors shows that Insomniac provides the best energy efficiency. From these results, we conclude that extending the voltage range below Vdd/2 will improve the energy efficiency for many processor designs.